Effects of smoking or baking procedures during sausage processing on the formation of heterocyclic amines measured using UPLC-MS/MS. (15th March 2019) - Yang, Diaodiao; He, Zhiyong; Gao, Daming; Qin, Fang; Deng, Shaolin; Wang, Peng; Xu, Xinglian; Chen, Jie; Zeng, Maomao
Highlights: Eight (five free and seven bound) HAs at levels up to hundreds of ng/g were detected in sausage. Smoking could increase HAs to more than twice levels found in baked sausages. At higher baking temperatures, lower levels of HAs were found in baked sausages. At higher smoking temperatures, higher levels of HAs were found in smoked sausages. The highest total HAs was 422 ± 17.5 ng/g in sausages smoked at 60 °C. Abstract: We used an UPLC-MS/MS method to investigate the effects of smoking or baking on the formation of heterocyclic amines (HAs) in sausage processing. We used principal component analysis (PCA) to differentiate the chemical composition, pH and colour of the processed sausages. We detected and quantified eight types of HAs (PhIP, DMIP, Phe-P-1, IQ[4, 5- b ], 7, 8-DiMeIQx, AαC, harman and norharman) in sausages, finding total HA concentrations as high as 422 ± 17.5 ng/g. Higher smoking temperatures led to higher concentrations of total HA in smoked sausages (330 ± 8.19 to 422 ± 17.5 ng/g). On the contrary, higher baking temperatures created lower total HA concentrations in baked sausages (ranging from 139 ± 9.83 to 306 ± 0.92 ng/g). Our results demonstrated that HAs are produced even at low temperatures, which means that HAs should be controlled during sausage processing to minimise their formation.